Compare the Effect of Different Mental and Physical Training Methods on the Motor Function of Girls and Boys - Hamid Abbasi Bafghi; Farahnaz Ayatizadeh Tafti; mohamad Reza sadeghian shahi; Mohsen Vakilzadeh (University of Tehran, 2023)
Introduction: The purpose of this study was to compare the effect of different mental and physical training methods on the motor function of girls and boys.Methods: This study was quasi-experimental research. The statistical sample consisted of 80 male and female students of Boshruyeh City in equal numbers and with a mean age of 14±0.9 years old who were randomly assigned into four groups of 20 participants (Physical Training, Traditional Imagery, PETTLEP, and Control groups). The participants took part in the pre-test and then practiced for six weeks. After training, they participated in the acquisition test To analyze the data, one-way analysis of variance, two-way repeated measures analysis of variance, and LSD post hoc tests were used. A significance level of 0.05 was considered.Results: The results showed that there is a significant difference in motor function between boys and girls based on the different training methods. The motor function of both genders has improved significantly in the Physical Training and PETTLEP groups. Also, the level of motor function of girls and boys was significantly better in the PETTLEP group than in other groups. In addition, Boys in PETTLEP have better motor function than girls.Conclusion: The findings of the study highlight the importance and necessity of paying attention to the methods of physical training and PETTLEP in improving the motor function of students according to their gender. An increase in the motor function of students can be expected especially for boys, by adding the PETTLEP in their training plan.